LAND CREATIONS AND FARMING SYSTEM TO INCREASE OF RICE PRODUCTIVITY AND FARMER’S INCOME (CASE STUDY IN BATANG TAMPO IRRIGATION SYSTEM - LINTAU BUO) - Ayendra Asmuti; Agita Tjandra (Jurusan Tanah Fakultas Pertanian Universitas Andalas, 2020)
It is estimated that around 95 percent of national rice production is supplied from paddy fields, so the paddy fields is very strategic in national food securities. Therefore, the potential carrying capacity and productivity of rice fields must be maintained and developed. But on the contrary the productivity of paddy fields in Sub Das Tampo, Lintau Buo Utara, Tanah Datar District, West Sumatra, there is an indication of a decrease in paddy productivity in the last 10 years (Agita and Ayendra 2018). Decreased paddy productivity is indicated as a result of 1.) Drainage or nutrient deficit due to harvest carried out more than what is given through fertilization or addition of nutrients from irrigation water, 2). Excess or lack of certain nutrients due to unbalanced fertilization, 3). Decreased of soil organic content in the land and 4). Decrease in the quality of rice field management, especially: a). the use of inorganic fertilizers which causes low organic matter content and soil texture becomes porous quench, so it is less able to hold water, b). use of rotary plow in tillage for a long time which causes the processing layer and the depth of the root zone to become shallower ( into 10-15 cm), c). less intense of crop maintenance. This research was carried out by creating of soil tillage from 10-15 cm to 20-25 cm using a plow and increasing of organic matter by adding manure of 50 tons / ha (5% soil tillage zone ) to the rice fields in the Farmers Group of Tanjung Mutiara in Tampo Irrigation System, Nagari Lubuk Jantan , Kecamatan Lintau Buo Utara. The results of the study showed an increase in land productivity from an average of 3.2 tons / ha to 4.6 tons / ha and increase farmers' income by Rp 1.200.000 / ha.Key words : land creation, soil tillage, productivity